Primary erythromelalgia: a clinical diagnosis - Maria Sousa-Dias; Mariana Meneses; Nádia Rodrigues (Publicaciones Permanyer, 2023)
Erythromelalgia is a rare chronic disorder characterized by a triad of intermittently red, hot and painful extremities. The syndrome usually affects the lower extremities with symmetrical cutaneous findings, but may also involve the upper extremities and, rarely, the face and present with unilateral involvement only.